HALOXYFOP-P-METHYL IN THE CONTROL OF BRACHIARIA DECUMBENS IN EUCALYPTUS - Bizao de Assis, Henrico Luiz [UNESP]; Cesarin, Anne Elise [UNESP]; Nepomuceno, Mariluce Pascoina [UNESP]; Salgado, Tiago Pereira; Costa Aguiar Alves, Pedro Luis da [UNESP] (Univ Federal Lavras-ufla, 2015)
Eucalyptus plantations in Brazil expanded to the Midwest region of the country in areas previously occupied by pastures, especially of Brachiaria decumbens (signal grass), making it the main weed in eucalyptus plantation. This work aimed to evaluate the efficiency of haloxyfop-P-methyl to control B. decumbens infesting eucalyptus seedlings. This experiment was set up in three situations: monoculture eucalyptus, eucalyptus in coexistence with B. decumbens and the weed cultivated alone. Haloxyfop-p-methyl was applied 67 days after plating the seedlings at doses of 0; 48 and 96 g.i.a.ha(-1). Only the highest dose (96 g.i.a.ha(-1)) of haloxyfop-p-methyl provided good weed control. The herbicide, at the tested doses, was selective for eucalyptus and the relationship between eucalyptus and B. decumbens resulted in negative interference for both species.
Keywords: Urochloa decumbens; Eucalyptus urograndis; Competition; Control